2014
DOI: 10.1074/jbc.m114.583302
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mechanism of Negative Regulation of 1,25-Dihydroxyvitamin D3-induced 25-Hydroxyvitamin D3 24-Hydroxylase (Cyp24a1) Transcription

Abstract: Background: CYP24A1 is the principal enzyme involved in the catabolism of 1,25(OH) 2 D 3 . Results: The SWI/SNF complex and PRMT5 converge at the transcriptional level to control 1,25(OH) 2 D 3 -induced Cyp24a1 gene expression. Conclusion: PRMT5-mediated repression represents a novel mechanism of negative regulation of Cyp24a1. Significance: Our study reveals key factors involved in the regulation of 1,25(OH) 2 D 3 catabolism and therefore in the control of calcium homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 60 publications
0
20
0
1
Order By: Relevance
“…Thus, there appears to be a direct negative feedback loop between interferon signaling and expression of extracellular matrix genes by osteoblasts. Interestingly, PRMT5 has been shown to repress 1, 25-dihydroxy vitamin D3 (1,25(OH) 2 D 3 ) catabolism by negatively regulating Cyp24a1, a 25-hydroxyvitamin D3 24-hydroxylase [37]. Upon PRMT5 inhibition, levels of Cyp39a1, 24 S- hydroxycholesterol 7-alpha-hydroxylase, an enzyme involved in Vitamin D precursor metabolism were increased (0.9 fold, log2FC).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, there appears to be a direct negative feedback loop between interferon signaling and expression of extracellular matrix genes by osteoblasts. Interestingly, PRMT5 has been shown to repress 1, 25-dihydroxy vitamin D3 (1,25(OH) 2 D 3 ) catabolism by negatively regulating Cyp24a1, a 25-hydroxyvitamin D3 24-hydroxylase [37]. Upon PRMT5 inhibition, levels of Cyp39a1, 24 S- hydroxycholesterol 7-alpha-hydroxylase, an enzyme involved in Vitamin D precursor metabolism were increased (0.9 fold, log2FC).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the genes constituting this panel serve as biomarkers for efficacy, prognosis, diagnosis, disease progression (targeting inflammation, oxidative stress and vesiculation gene networks) and response to therapy [43,44,45,46,47,48,49,50,51,52,53,54,55,56,57]. Vitamin D mediated genetic networks such as those identified in our study, for example inflammation, oxidative stress and membrane vesicle biogenesis pathways in 143B cells, shed insight into the mechanism(s) underlying antineoplastic effects of vitamin D in human OS.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, recent studies in liver stellate cells suggested that 1,25(OH) 2 D 3 -mediated repression of a profibrotic gene expression program induced by TGFβ does not involve the apparent recruitment of corepressors SMRT and NCoR (162). In addition to SRC1, CBP and MED1, Brahma-related gene 1 (BRG1), an ATPase that is a component of the SWI/SNF chromatin remodeling complex, has been reported to play a fundamental role in 1,25(OH) 2 D 3 induced transcription (163). C/EBP and BRG1 are components of the same complex and are recruited to the C/EBP site of the CYP24A1 gene by 1,25(OH) 2 D 3 .…”
Section: The Vitamin D Receptor and Genomic Mechanisms Of Actionmentioning
confidence: 99%